Measurements of Fusion Reactions of Low-Intensity Radioactive Carbon Beams on 12C and their Implications for the Understanding of X-Ray Bursts - Carnelli, Patricio Francisco Florencio (2014)
The interaction between neutron-rich nuclei plays an important role for understanding the reaction mechanism of the fusion process as well as for the energy production through pycnonuclear reactions in the crust of neutron stars. We have performed the first measurements of the total fusion cross sections in the systems 10,14,15C+12C using a new active target-detector system. In the energy region accessible with existing radioactive beams, a good agreement between the experimental and theoretical cross sections is observed. This gives confidence in our ability to calculate fusion  cross sections for systems which are outside the range of today´s radioactive beam facilities.